Cardioprotective Angiotensin-(1–7) Peptide Acts as a Natural-Biased Ligand at the Angiotensin II Type 1 Receptor. Issue 6 (December 2016) - Galandrin, Ségolène; Denis, Colette; Boularan, Cédric; Marie, Jacky; M'Kadmi, Céline; Pilette, Claire; Dubroca, Caroline; Nicaise, Yvan; Seguelas, Marie-Hélène; N'Guyen, Du; Banères, Jean-Louis; Pathak, Atul; et al.
Abstract : Hyperactivity of the renin–angiotensin–aldosterone system through the angiotensin II (Ang II)/Ang II type 1 receptor (AT1-R) axis constitutes a hallmark of hypertension. Recent findings indicate that only a subset of AT1-R signaling pathways is cardiodeleterious, and their selective inhibition by biased ligands promotes therapeutic benefit. To date, only synthetic biased ligands have been described, and whether natural renin–angiotensin–aldosterone system peptides exhibit functional selectivity at AT1-R remains unknown. In this study, we systematically determined efficacy and potency of Ang II, Ang III, Ang IV, and Ang-(1–7) in AT1-R–expressing HEK293T cells on the activation of cardiodeleterious G-proteins and cardioprotective β-arrestin2. Ang III and Ang IV fully activate similar G-proteins than Ang II, the prototypical AT1-R agonist, despite weaker potency of Ang IV. Interestingly, Ang-(1–7) that binds AT1-R fails to promote G-protein activation but behaves as a competitive antagonist for Ang II/Gi and Ang II/Gq pathways. Conversely, all renin–angiotensin–aldosterone system peptides act as agonists on the AT1-R/β-arrestin2 axis but display biased activities relative to Ang II as indicated by their differences in potency and AT1-R/β-arrestin2 intracellular routing. Importantly, we reveal Ang-(1–7) a known Mas receptor-specific ligand, as an AT1-R–biased agonist, selectively promoting β-arrestin activation while blocking the detrimental Ang II/AT1-R/Gq axis. This original pharmacological profile of Ang-(1–7) at AT1-R, similar to that of synthetic AT1-R–biased agonists, could, in part, contribute to its cardiovascular benefits. Accordingly, in vivo, Ang-(1–7) counteracts the phenylephrine-induced aorta contraction, which was blunted in AT1-R knockout mice. Collectively, these data suggest that Ang-(1–7) natural-biased agonism at AT1-R could fine-tune the physiology of the renin–angiotensin–aldosterone system. Abstract : Supplemental Digital Content is available in the text.